The necessity of Introducing the One Health Concept to Health Workforce and Veterinary Workforce in Addressing Zoonotic Threats - Thursina, Tanrypada (BKM Public Health and Community Medicine, 2024)
In recent years, zoonoses have continued to pose a threat to global health, including in Indonesia. Avian influenza infections, rabies cases that remain endemic in many regions, and the COVID-19 pandemic are concrete examples of the dangers of zoonoses. These health issues can be prevented and addressed through cross-sectoral collaboration and the implementation of the One Health concept. The One Health concept emphasizes the interconnection between the health sector, animal health, and the environmental sector. One Health concept also promotes essential cross-sectoral collaboration in the prevention and control of zoonoses. As a concept that emphasizes various sectors to address the complex issue of zoonoses, it significantly aids in the rapid and accurate response to case reports and outbreak investigations. However, many health workers and veterinary health workers are still unaware of or do not understand this concept. The lack of knowledge among these workers about the One Health concept can be problematic in managing zoonotic cases in the future, especially given the changing epidemiology of many zoonotic diseases. Despite cross-sectoral collaboration having existed, the absence of the introduction and implementation of the One Health concept results in fragmented and uncoordinated responses to zoonotic case reports and makes the handling less effective and proactive. Therefore, it is necessary to systematically introduce this concept to health and veterinary health workers through integrated and sustainable educational programs. Providing education about One Health not only enhances the skills and capacity of health and veterinary health workers but also strengthens the national health system. Comprehensive introduction and training on One Health must become a priority to ensure that zoonoses do not continue to develop and pose a threat to public health in Indonesia.